Matoš’s modernistic version of a fairy tale - Katušić, Bernarda (Anafora, 2022)
The paper aims to show that in his prose oeuvre, Matoš appropriates the typical fairy tale elements, unifies different fairy tale traditions and adapts them pursuant to the symbolist poetics in order to create his own variation of a modernist literary fable (Kunstlermärchen).